"They seemed to be like cogs working in different directions": a longitudinal qualitative study on Long COVID healthcare services in the United Kingdom from a person-centred lens - Chao Fang; Sarah Akhtar Baz; Laura Sheard; J. D. Carpentieri (BMC, 2024)
Abstract Background The COVID-19 pandemic has presented significant challenges to the already over-stretched healthcare system in the United Kingdom (UK). These challenges are particularly pronounced for people living with the novel condition of Long COVID (LC) as they often face persistent and fluctuating symptoms, encountering prolonged uncertainty when seeking medical support. Despite a growing understanding of the healthcare challenges associated with LC, existing qualitative studies have predominantly focused on individual experiences rather than examining the structural aspects of healthcare. Methods A longitudinal qualitative study with 80 participants and 12 healthcare practitioners was conducted in the UK to explore the healthcare experiences of those with LC. In total, 178 interviews (with attrition) were collected across two rounds, from November 2021 to March 2022, and from June to October 2022. Results Embracing a person-centred framework that recognises and nurtures interconnected individual, relational, and existential needs, we investigated healthcare experiences related to LC across primary, secondary, and specialist integrated care. Using this perspective, we identified three overarching themes. Theme 1 addresses the persistent hurdle of accessing primary care as the initial point of contact for LC healthcare; Theme 2 underscores the complexity of navigating secondary care; and Theme 3 encapsulates the distinctive challenges of developing LC integrated care. These themes are interlinked, as people with LC often had to navigate or struggle between the various systems, with practitioners seeking to collaborate across the breadth of their professional responsibilities. Conclusion From a person-centred approach, we were able to identify the needs of those affected by lasting LC symptoms and comprehend how health services intricately influence these needs. The focus on healthcare systems also captures the nuanced impact that continuing healthcare struggles can have on people's identity. As such, our findings provide evidence to inform a more effective and sustainable delivery of person-centred care for people with LC across various healthcare settings and over time.